المسائل الفقهية التي خالف فيها ابن تيمية المذاهب الأربعة ''الطلاق أنموذجا - زين, مريم; مجور, مريم (جامعة الوادي - University of Eloued, 2014)
This research studies a doctrinal issues is which ibntaymiyyah disagree with the four imams particularly ,we divorce that includes an introduction ,two chapters and a conclusion. At the onset we have analyzed the opinions of achykhibntaymiyyah and comparing then to four doctrines in term of the first chapter ; the theoretical part of the study which is divided into two sections concerning the firstsection we mentions, in it the scientific and the personal lives, whit we have mentioned in the second section the scientific and the personal lives of four imams in the second chapters we have the practical part that parted into two sections, the first section concerns generally different doctrinal issues of ibntaymiyyah in where he didn’t agree with the four imams, as we just mentioned some issues from each door, though we have mentioned in the second chapter two issues of divorce which are the divorce in time of .menstruation and the third verbal divorce. In the short and long, the most important results we reminded thatibntaymiyyah’s speeches con corning the divorce are hot based on fancy and appétit ,however they must based and .taking from religious references.
ليسانس